Molecular Docking and Molecular Dynamics Analysis of Phytochemical Compounds from Nutmeg Fruit (Myristica fragrans Houtt.) on Androgen Receptor (4K7A) as Anti-Alopecia Therapy - Yasir, Angga Saputra; Sari, Indah Puspita (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Androgenetic alopecia (AGA) represents the most prevalent hair loss form, necessitating natural treatment alternatives. This study investigated nutmeg (Myristica fragrans Houtt.) phytochemicals as anti-alopecia agents through molecular docking and dynamics simulations. Thirty-four compounds, including native ligands (minoxidil, finasteride) and 32 nutmeg-derived compounds, were evaluated against androgen receptor (PDB: 4K7A) using AutoDock4.0 and GROMACS 2024.2. Molecular docking validation achieved successful minoxidil redocking with 2.25 Å RMSD, confirming method reliability. Geranylgeraniol (ID: 33) demonstrated optimal results with -7.00 kcal/mol binding energy, nearly equivalent to finasteride (-7.19 kcal/mol) and superior to minoxidil (-4.85 kcal/mol). Geranylgeraniol formed strong hydrogen bonds with GLU793 at 1.77 Å distance, with nearby residues LEU862, TYR857, ARG854, LYS861, and LEU797. Twenty-five nanosecond molecular dynamics revealed stable complex formation with 0.23-0.25 nm RMSD values, indicating acceptable binding stability. RMSF analysis showed geranylgeraniol induced higher structural flexibility in specific regions, potentially enhancing biological activity. SASA analysis demonstrated lower surface area values (112.5 nm²), indicating improved stability versus minoxidil. These findings suggest geranylgeraniol possesses significant anti-alopecia potential with comparable finasteride efficacy and superior minoxidil performance.